2007
DOI: 10.2144/000112400
|View full text |Cite
|
Sign up to set email alerts
|

Validation of Rat Reference Genes for Improved Quantitative Gene Expression Analysis Using Low Density Arrays

Abstract: Real-time PCR has become increasingly important in gene expression profiling research, and it is widely agreed that normalized data are required for accurate estimates of messenger RNA (mRNA) expression. With increased gene expression profiling in preclinical research and toxicogenomics, a need for reference genes in the rat has emerged, and the studies in this area have not yet been thoroughly evaluated. The purpose of our study was to evaluate a panel of rat reference genes for variation of gene expression i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(16 citation statements)
references
References 20 publications
1
15
0
Order By: Relevance
“…We found that PPIB showed less variation than beta-actin and GAPDH in rat spleen tissue (Figure S2). PPIB as a reliable reference gene in rat spleen mRNA analysis was compatible with another previous report [17]. Thereafter, we used PPIB as a reference gene in subsequent studies.…”
Section: Resultssupporting
confidence: 66%
“…We found that PPIB showed less variation than beta-actin and GAPDH in rat spleen tissue (Figure S2). PPIB as a reliable reference gene in rat spleen mRNA analysis was compatible with another previous report [17]. Thereafter, we used PPIB as a reference gene in subsequent studies.…”
Section: Resultssupporting
confidence: 66%
“…Single reference gene normalization across developmental stages may be difficult because of the wide variation in expression at different developmental stages [14]. We show here a marked shift in the expression stability of several reference genes in the transition from neonatal to adult rat myocardium.…”
Section: Discussionmentioning
confidence: 72%
“…The set of reference genes examined in our study were chosen, because of their previous use to normalization changes in gene expression. For example, MAPK6 and GAPD have been found to be stable normalization genes in rat brain tissue (Cai et al 2007). Use of 18S RNA and actin have been highly published in the literature.…”
Section: Discussionmentioning
confidence: 99%